ANALISIS PENGARUH PROGRAM PERTAMINA WAY TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN PADA PT KARYA MARANATHA ABADI DI TAHUNA - Dompas, Saartje Laoh (JBE (Journal of Business and Economics), 2013)
This study analyzes and test variables consist of tangible, reliability, assurance, responsiveness, empathy, customer satisfaction and customer loyalty. Analysis process performed by descriptive statistical analysis.  The test results that variables tangible, reliability, assurance, responsiveness and empathy significantly influence customer satisfaction and customer loyalty simultaneously, and customer satisfaction significantly influence customer loyalty.